Short- and middle-range order structures of KNbO3 nanocrystals. (21st August 2019) - Yoneda, Yasuhiro; Kunisada, Ryoichi; Chikata, Tsukasa; Ueno, Shintaro; Fujii, Ichiro; Nagata, Hajime; Ohara, Koji; Wada, Satoshi
Abstract: The atomic-scale structure of KNbO3 nanocrystals with the particle size of 115 ∼165 Å has been studied by combining Rietveld refinement and the atomic pair-distribution function (PDF) technique. We performed high-energy synchrotron X-ray scattering to extract short- and middle-range order structures. The unit cell size of the KNbO3 nanocrystals expanded as the particle size was reduced. PDF analysis of the whole nanocrystals in the initial phase of the crystal growth showed that it is close to a rhombohedral structure at the short-range order, tetragonal structure at the middle-range order, and cubic structure at the long-range order. The local structure is asymptotic to the average structure as the fitting range is elongated. The size of the region in which the local structure is same as that of the bulk, we named this the coherent length, is closely related to the average structure.